Change in Lung Fluid Volume during Exercise in Patients with Exercise-Induced Mitral Regurgitation - Teruhiko Imamura; Masakazu Hori; Shuhei Tanaka; Nikhil Narang; Koichiro Kinugawa (Medicina, 2022)
Exercise-induced mitral regurgitation (MR) can be diagnosed during stress echocardiography testing. Remote dielectric sensing (ReDSTM) is a noninvasive electromagnetic-based modality to measure lung fluid levels. The change in lung fluid levels in patients with MR during stress echocardiography remains unknown. Patients with symptomatic MR at baseline and suspected worsening exercise-induced MR underwent stress echocardiography. ReDS values were measured before and after the tests. A total of four patients (ages ranging between 74 and 84 years old, three women) underwent stress echocardiography testing using a bicycle ergometer. In patient A, MR effective regurgitant orifice area (EROA) remained unchanged and ReDS values decreased. EROA increased significantly with a small incremental change in ReDS values in patient B and patient C, who underwent valve repair with MitraClip later. Patient D had a mild increase in MR EROA but a considerable increase in ReDS values (from 22% to 32%), and eventually received valve repair with MitraClip. The ReDS system may be a complementary tool to conventional stress echocardiography in the evaluation of clinically significant MR and considering mitral valve intervention.